Shifts in Estuarine Macroinvertebrate Communities Associated With Water Quality and Climate Change - Goulding, Thomas; Sousa, Pedro M.; Silva, Gilda; Medeiros, João Paulo; Carvalho, Frederico; Metelo, Inês; Freitas, Catarina; Lopes, Nuno; Chainho, Paula; Costa, José Lino (Frontiers in Marine Science, 2021)
The present work aims to identify changes in the macroinvertebrate community of the Tagus estuary (Portugal) due to improvements in water quality and to climate change. Data was collected over a period of 16 years (1998–2014) from different sites located along the estuarine gradient. The AZTI Marine Biotic Index (AMBI) was used to assess the ecological quality status based on benthic invertebrate communities and identify possible variations associated with changes in water quality. The overall distribution of each species was examined to detect possible changes associated with climate, based on species’ affinity for more temperate or subtropical climates. Results demonstrate that there was an overall improvement of AMBI scores during the assessment period. The analysis of the geographical distribution of benthic species seems to indicate that there has been an increase of species which prefer subtropical climates in the shallower waters of the estuary, whereas in the deeper estuarine sections the propensity is for species that prefer temperate climates.